Comparison of human chromosome 6p25 with mouse chromosome 13 reveals a greatly expanded ov-serpin gene repertoire in the mouse. - Kaiserman, D; Knaggs, S; Scarff, K; Gillard, A; Mirza, G; Cadman, M; McKeone, R; Denny, P; Cooley, J; Benarafa, C; Remold-O'Donnell, E; Ragoussis, J; et al. (2002)
Ov-serpins are intracellular proteinase inhibitors implicated in the regulation of tumor progression, inflammation, and cell death. The 13 human ov-serpin genes are clustered at 6p25 (3 genes) and 18q21 (10 genes), and share common structures. We show here that a 1-Mb region on mouse chromosome 13 contains at least 15 ov-serpin genes compared with the three ov-serpin genes within 0.35 Mb at human 6p25 (SERPINB1 (MNEI), SERPINB6 (PI-6), SER-PINB9 (PI-9)). The mouse serpins have characteristics of functional inhibitors and fall into three groups on the basis of similarity to MNEI, PI-6, or PI-9. The genes map between the mouse orthologs of the Werner helicase interacting protein and NAD(P)H menadioine oxidoreductase 2 genes, in a region that contains the markers D13Mit136 and D13Mit116. They have the seven-exon structure typical of human 6p25 ov-serpin genes, with identical intron phasing. Most show restricted patterns of expression, with common sites of synthesis being the placenta and immune tissue. Compared with human, this larger mouse serpin repertoire probably reflects the need to regulate a larger proteinase repertoire arising from differing evolutionary pressures on the reproductive and immune systems.